Impaired attentional selection following lesions to human pulvinar: evidence for homology between human and monkey. - Snow, J; Allen, H; Rafal, R; Humphreys, G (2009)
We examined the contributions of the human pulvinar to goal directed selection of visual targets in 3 patients with chronic, unilateral lesions involving topographic maps in the ventral pulvinar. Observers completed 2 psychophysical tasks in which they discriminated the orientation of a lateralized target grating in the presence of vertically-aligned distracters. In experiment 1, where distracter contrast was varied while target contrast remained constant, the patients' contralesional contrast thresholds for discriminating the orientation of grating stimuli were elevated only when the task required selection of a visual target in the face of competition from a salient distracter. Attentional selectivity was restored in the patients in experiment 2 where target contrast was varied while distracter contrast remained constant. These observations provide the first evidence that the human pulvinar plays a necessary role in modulating physical saliency in attentional selection, and supports a homology in global pulvinar structure between humans and monkey.